The adherence of education reform to international education policy. A brief overview of the path from the General Law of the Education System (LOGSE) of 1990 to the Law for the Improvement of Education Quality (LOMCE) of 2013 - Cabrera Montoya, Blas (Historia y Memoria de la Educación, 2016)
The aim of this paper is to illustrate the continuities of educational reforms in the Spanish democracy, and especially between the General Law of the Education System (LOGSE) of 1990 and the Law for the Improvement of Education Quality (LOMCE) of 2013. In order to do so we will examine what we consider to be the three main concerns on which current educational patterns are based: first, the crisis of the traditional materials and symbolic functions of universal education systems under capitalism, which entails a slow transformation in mentalities regarding the social importance of education; secondly, the inevitable dependence of virtually all Spanish education legislation in democracy to the provisions of Article 27 of the Spanish Constitution of 1978; and finally, the greater role that the laws attribute to international assessment and accountability in Spain. This last point is the most important new feature of educational policy in the last twenty five years.